A minute primary gastric synovial sarcoma with ulcer: a case report - Kanako Yoshiyasu; Hiroshi Kono; Yudai Hojo; Yoshinori Ishida; Akio Tamura; Keisuke Nakai; Tadayuki Oshima; Hiroto Miwa; Hisashi Shinohara; Seiichi Hirota (BMC, 2021)
Abstract Background Synovial sarcomas are a rare type of high-grade sarcomas with unknown cell origin. They arise predominantly in the soft tissues but rarely in the stomach. We recently encountered a rare case of minute gastric synovial sarcoma. Case presentation A 61-year-old Japanese woman was pointed out edematous erosion at the body of the stomach. Biopsy specimen showed dense proliferation of spindle-shaped tumor cells mixed with smooth muscle fibers of the muscularis mucosae. Although the definite histological diagnosis was undetermined, the patient underwent laparoscopic wedge resection of the stomach. Histological examination of the resected sample revealed that the maximum diameter of the tumor was only 6 mm and that dense proliferation of rather uniform spindle tumor cells were observed mainly in the submucosa. Immunohistochemistry showed that they were positive for pan-keratin, CD99 and TLE1. SS18-SSX fusion-specific antibody gave diffuse positive staining to the tumor cells, and analysis using mRNA extracted from paraffin sections revealed that the tumor had SS18-SSX1 fusion gene. Thus, it was diagnosed as gastric synovial sarcoma, monophasic fibrous type. Conclusions Primary synovial sarcoma of the stomach is rare and only 47 cases have been reported in the English literature to date. The maximum diameter of the lesion of our case was 6 mm which is the smallest among them.